2017
DOI: 10.2105/ajph.2016.303561
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a Large-Scale Television Campaign With Exclusive Breastfeeding Prevalence in Vietnam

Abstract: Mass media should be part of comprehensive programs to promote EBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Previous studies showed that breastfeeding education helped to improve breastfeeding knowledge and breastfeeding practices (Oche, Umar, & Ahmed, 2011;Radhakrishnan & Balamuruga, 2014;Shi et al, 2008). Breastfeeding beliefs, knowledge and self-efficacy can also be improved through interpersonal communications and mass media campaigns (Nguyen et al, 2016;Nguyen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that breastfeeding education helped to improve breastfeeding knowledge and breastfeeding practices (Oche, Umar, & Ahmed, 2011;Radhakrishnan & Balamuruga, 2014;Shi et al, 2008). Breastfeeding beliefs, knowledge and self-efficacy can also be improved through interpersonal communications and mass media campaigns (Nguyen et al, 2016;Nguyen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to clearly articulate and communicate the benefits of exclusive breastfeeding to mothers [ 28 ], emphasizing the fact that it provides sufficient quantity and nutritional quality for a growing baby. Reliable health information should also be made available on trusted websites, given that the internet is an important source of health information for educated mothers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another hope of the participants is the massive advertisement for exclusive breastfeeding in the media. The results of research by Tuan.T Nyuyen , MD et al (2017) who studied the Television Campaign with Exclusive Breastfeeding showed excellent results related to exposure to breastfeeding campaigns through television media with exclusive breastfeeding 20 . In addition, the other research show that mother who saw breastfeeding ads on television and heard about breastfeeding on the radio had a positive perception about breastfeed their children for longterm health with the percentage 94% dan 100% respectively compare to the others 13 .…”
Section: Discussionmentioning
confidence: 99%